A Novel Approach by Spark Plasma Sintering to the Improvement of Mechanical Properties of Titanium Carbonitride-Reinforced Alumina Ceramics - Magdalena Szutkowska (Molecules, 2021)
Ti(C,N)-reinforced alumina-zirconia composites with different ratios of C to N in titanium carbonitride solid solutions, such as Ti(C0.3,N0.7) (C:N = 30:70) and Ti(C0.5,N0.5) (C:N = 50:50), were tested to improve their mechanical properties. Spark plasma sintering (SPS) with temperatures ranging from 1600 °C to 1675 °C and pressureless sintering (PS) with a higher temperature of 1720 °C were used to compare results. The following mechanical and physical properties were determined: Vickers hardness, Young’s modulus, apparent density, wear resistance, and fracture toughness. A composite with the addition of Ti(C0.5,N0.5)n nanopowder exhibited the highest Vickers hardness of over 19.0 GPa, and its fracture toughness was at 5.0 Mpa·m1/2. A composite with the Ti(C0.3,N0.7) phase was found to have lower values of Vickers hardness (by about 10%), friction coefficient, and specific wear rate of disc (Wsd) compared to the composite with the addition of Ti(C0.5,N0.5). The Vickers hardness values slightly decreased (from 5% to 10%) with increasing sintering temperature. The mechanical properties of the samples sintered using PS were lower than those of the samples that were spark plasma sintered. This research on alumina–zirconia composites with different ratios of C to N in titanium carbonitride solid solution Ti(C,N), sintered using an unconventional SPS method, reveals the effect of C/N ratios on improving mechanical properties of tested composites. X-ray analysis of the phase composition and an observation of the microstructure was carried out.